Research on the tax support policy for implementing the Extended Producer Responsibility – Taking End-of-Life Vehicle Collecting and Dismantling Enterprises as an Example - Huo Lulu; Wang Jia; Huang Yonghe; Li Yuke; Pan Wei; Li Zhenbiao; Shi Hong (E3S Web of Conferences, 2021)
The Extended Producer Responsibility (EPR) is an important system for improving resource reuse rate and reducing waste pollution to the environment. Aiming at automobile products, this article takes end of-life vehicles collecting and dismantling enterprises as an example. By studying the support from tax support policy, tax incentives are provided to those enterprises that meet safety and environmental protection requirements. In this way, it can guide enterprises to improve safety and environmental protection and reduce corporate pressure from taxation. This article also predicts the effect of energy conservation and environmental protection after the implementation of tax support policy and demonstrates the importance of tax support policy of implementing the EPR.